Critical Thinking in Asynchronous Courses: Practical Suggestions - Steven HALLMAN; Linda Lee MASSOUD; Daniel TOMIUK (Communications of International Proceedings, 2021)
Although jobs in the 21st century will require high degrees of collaboration, communication, and critical thinking, our educational system is moving farther toward asynchronous learning that does not promote these skills without unique intervention by the course designer. Assignment processes that can promote these important skills include specialized multiple-choice questions, a variety of discussion board assignments, group projects, and experiential learning. Each of these assignment types can be deployed through the common Learning Management Systems (LMS’s) with appropriate instructions, rubrics, and peer/instructor feedback methodology. The purpose of this paper is to share numerous strategies for achieving these goals satisfactorily.
Keywords: Critical Thinking; Asynchronous Learning; Asynchronous Online Discussions (AOD); Online education.